Profiling of a pitcher's performance with a smart baseball: A case report - Doljin, B.; Jeong, K.; Kim, Y. K.; Fuss, F. K. (Proceedings, 2020)
A pitcher`s action, when delivering a fastball, was analyzed from the data provided by a smart baseball. The spin rate at the release of the ball was merely 15.7 rps, however, the peak torque was excessively high, namely 0.396 Nm. The reason why the pitcher was not able to translate the torque entirely to angular kinetic energy and this to the spin rate was that the spin axis changed its direction suddenly three times when moving across the ball`s surface. This resulted in angles between torque and angular velocity vectors of greater than 90°, high precession and precession torque, and negative spin torques, causing a very low efficiency (5.4%) and a slow spin rate at the release of the ball.